Climate, carbon, and soil stability: a key link in coffee-growing landscapes of the Peruvian Amazon - Romero Chávez, Lorena Estefani (2026)
Introduction: Coffee cultivation in the Central Peruvian Amazon, one of the country's most important production regions, faces increasing challenges from soil degradation and climate change impacts. This study aimed to evaluate the influence of the altitudinal gradient on soil organic carbon (SOC) stocks and soil erodibility (K index) in coffee-growing systems. Methods: Three altitudinal zones were established for sampling (0–20 cm depth): zone 1 (900–1200 m.a.s.l.), zone 2 (1201–1400 m.a.s.l.), and zone 3 (1401–1600 m.a.s.l.). Within these zones, physical and chemical soil properties were analyzed, and SOC and soil erodibility (K index) values were calculated. Results: The results revealed a direct and statistically significant relationship between altitude and carbon sequestration capacity. Zone 3 exhibited the highest SOC (63.19 t·ha⁻¹) and organic matter (OM) content (5.49%), compared with zone 1 (37.56 t·ha⁻¹). This difference is attributable to the climatic conditions at higher elevations, characterized by greater precipitation and lower temperatures. Structural equation modeling (SEM) indicated that increasing altitude enhances SOC (b = 0.42), which in turn improves the soil structural stability index (SI) (R² = 0.87) and reduces the K index (b = –0.38). Overall, the findings demonstrate that organic carbon acts as a key mediator between topography, soil texture, and susceptibility to erosion. The altitudinal gradient thus represents a major controlling factor influencing the health and structural stability of coffee soils. Discussion: These results highlight the need to implement site-specific soil management practices, emphasizing intensive conservation strategies in low-altitude coffee-growing systems to mitigate accelerated erosion and ensure long-term production sustainability under changing climatic conditions.